2016
DOI: 10.1186/s13046-016-0337-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-539 inhibits prostate cancer progression by directly targeting SPAG5

Abstract: BackgroundWe conducted multiple microarray datasets analyses from clinical and xenograft tumor tissues to search for disease progression-driving oncogenes in prostate cancer (PCa). Sperm-associated antigen 5 (SPAG5) attracted our attention. SPAG5 was recently identified as an oncogene participating in lung cancer and cervical cancer progression. However, the roles of SPAG5 in PCa progression remain unknown.MethodsSPAG5 expression level in clinical primary PCa, metastatic PCa, castration resistant PCa, neuroend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 38 publications
11
92
0
Order By: Relevance
“…Gu et al (39) reported that miR-539 expression is decreased in thyroid cancer tissues and cell lines. In addition, consistent with these results, low expression levels of miR-539 was observed in nasopharyngeal carcinoma (21) and prostate cancer (20). The high frequency of miR-539 downregulation in these types of human cancer suggested that miR-539 may be a novel marker for the diagnosis and prognosis of specific cancers.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Gu et al (39) reported that miR-539 expression is decreased in thyroid cancer tissues and cell lines. In addition, consistent with these results, low expression levels of miR-539 was observed in nasopharyngeal carcinoma (21) and prostate cancer (20). The high frequency of miR-539 downregulation in these types of human cancer suggested that miR-539 may be a novel marker for the diagnosis and prognosis of specific cancers.…”
Section: Discussionsupporting
confidence: 75%
“…To date, few genes have been validated as direct targets of miR-539, including sperm associated antigen 5 in prostate cancer (20), cyclin dependent kinase 4 in nasopharyngeal carcinoma (21), matrix metalloproteinase 8 in osteosarcoma (22) and caspase recruitment domain family member 11 in thyroid cancer (39). In the present study, SOX4 was validated as a novel direct and functional target of miR-539 in CRC.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Notably, SPAG5 has been shown to promote the proliferation, migration and invasion of various cancer cells. Inhibition of SPAG5 reduces the growth of prostate cancer cells in vitro and in vivo . SPAG5 overexpression promotes the proliferation and reduces the apoptosis of bladder urothelial carcinoma cells .…”
Section: Discussionmentioning
confidence: 99%